Características limnológicas da bacia hidrográfica do córrego Rico, Jaboticabal, SP - Iha, Danilo Sinhei (2010)
Evaluation of quality and quantity of water contributes to the strategic decisionmaking policies and techniques to ensure the potential use of this resource for agriculture, industry, animal watering and for human consumption. In order to assist the governing of the Rico stream watershed to create mechanisms and effective action to combat pollution from this resource this study was conducted. In 2006 the treatment sewage plant in the city of Monte Alto was established in this basin. The city of Jaboticabal, that uses the water of the stream Rico for human consumption, is located dowstream of this plant. Chemical, physical and microbiological analysis, were carried out in various parts of this basin. There was a significant variation in the water quality in this watershed between the dry and wet stations. It is concluded that the tributary that drains the area of the town of Monte Alto and its treatment sewage plant impairs the quality of water in this basin.